Gastroesophageal reflux disease and odds of head and neck squamous cell carcinoma in North Carolina. (9th October 2015) - Busch, Evan L.; Zevallos, Jose P.; Olshan, Andrew F.
Abstract : Objectives/Hypothesis: Exposure to excess gastric acid resulting from gastroesophageal reflux disease, also known as acid reflux or heartburn, might contribute to initiation of head and neck squamous cell carcinoma, particularly laryngeal cancer. Prior epidemiologic studies have reported inconsistent results. We sought to clarify this relationship using an observational study with a larger available sample size and better‐characterized exposure information than most prior studies. Study Design: A population‐based case‐control study of head and neck cancer in North Carolina with 1, 340 newly diagnosed cases and 1, 378 controls matched on age, race, and sex. Methods: We used unconditional logistic regression to examine associations between self‐reported heartburn and development of overall head and neck cancer as well as development of cancer at specific tumor sites. Subgroup analysis by smoking and alcoholic drinking status was used to make comparisons with a previous study that used a similar study design. Results: Overall, an increased odds of head and neck cancer was not associated with either self‐reported history of heartburn symptoms (odds ratio = 0.85; 95% confidence interval 0.68, 1.06) or self‐reported medical diagnosis of GERD (OR = 0.89; 95% CI 0.71, 1.11). These patterns held for specific tumor sites. For laryngopharyngeal cancer, we did not detect any associations regardless of joint smoking and alcoholic drinking status. Conclusion: Gastroesophageal reflux does not appear to play a role in development of head and neck cancer. Level of Evidence: 3b. Laryngoscope, 126:1091–1096, 2016